Failure of refractory masonry material under monotonic and cyclic loading – Crack propagation analysis. (13th September 2021) - Andreev, K.; Yin, Y.; Luchini, B.; Sabirov, I.
Graphical abstract: Highlights: Knoop hardness interprets microstructural measurements and stress–strain data. Monotonic failure is more brittle, with same trans -granular failure in both modes. Monotonic crack aligns with less energy consuming grain-matrix interface. Differences arise due to lower energy input and matrix pre-cracking in the cyclic mode. Abstract: Refractory masonry (refractories) is exposed to in-service loads of different types. To rationalise the masonry design and failure analysis, differences of failure under cyclic and monotonic loading were studied. For samples of silica refractories tested in wedge splitting set-up global failure parameters and crack trajectories were assessed. Under cyclic loading, higher fracture energy and lower brittleness at failure were seen. Cracks of different modes had similar non-linearity and branching. However, the size and microstructural characteristics of the fracture process zone was different. In addition, higher energy dissipation during cyclic loading is promoted by repetitive friction events along the crack trajectory.